PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN KERJASAMA DAN PRESTASI BELAJAR MATEMATIKA - Ardiana; Johanes Sapri (UNIB Press, 2024)
This study aims to describe the application of the Team Assisted Individualization (TAI) Type Cooperative Learning model to improve cooperation and learning achievement, as well as the effectiveness of the Cooperative Learning Model implementation. This research was conducted using Classroom Action Research (CAR) and continued with a quasi-experimental. The data collection technique in this study used an observation sheet to measure the teacher's ability to apply the Cooperative Type Team Assisted Individualization (TAI) model, and to measure the increase in student cooperation, as well as a test to measure student achievement. The research data analysis technique used mean analysis and t-test. Based on the results of research data processing, it is concluded that the application of the Team Assisted Individualization (TAI) Cooperative Learning Model can improve student collaboration, and learning achievement, and the application of the Team Assisted Individualization (TAI) Cooperative Learning Model is effective in improving student achievement in Mathematics. Based on the conclusions of the research results, suggestions are proposed as follows: teachers must provide innovation in learning and are required to have a complete understanding of learning concepts about learning models such as the Team Assisted Individualization (TAI) Cooperative Learning Model and for further researchers to improve this research by referring to the shortcomings -existent deficiencies in order to obtain better results